Electrical properties of Mg2+ ion-conducting PEO: P(VdF-HFP) based solid blend polymer electrolytes. (21st September 2022) - Shenbagavalli, S.; Muthuvinayagam, M.; Revathy, M.S.
Abstract: Mg 2+ ion-conducting solid blend polymer electrolytes (SPEs) based on PEO: P(VdF-HFP) are prepared by solution casting technique using DMF as solvent. The X-ray diffraction analysis (XRD) confirms the decrease in crystalline phase of polymer electrolytes due to the addition of salt. The complex formation between polymers and salt is confirmed by Fourier transform infrared spectroscopy (FTIR) analysis. Morphological analysis shows the existence of interconnected micro-pores that enhances the mobility of Mg 2+ ions. The polymer electrolyte (PEO:P(VdF-HFP):MgBr2 )(90:10:15) has higher ionic conductivity of 3.90 × 10 −4 S/cm at room temperature. For all solid blend polymer electrolytes, the total ionic transference number has been observed to be 0.98–0.99 range. The polymer electrolytes exhibit maximum electrochemical stability of 1.86 V. The cyclic voltammetry (CV) performance of the prepared EDLC reveals the increase in specific capacitance as the scan rate decreases. According to charge-discharge studies, the cyclic retention of the EDLC is maintained to be ∼84.2% even after 500 cycles. Graphical abstract: Image 1 Highlights: Highly Magnesium ion conducting solid blend polymer electrolytes are prepared with PEO/P(VdF-HFP) by solution casting technique. The XRD, FTIR and SEM analysis confirm the complexation and functional groups present in the electrolytes. The maximum ionic conductivity was observed as 3.90 × 10 −4 S/cm at room temperature for the sample containing 15 wt% MgBr2 . The Electrochemical double-layer capacitor(EDLC) shows maximum specific capacitance ( C s p ) of 8.92 F/g. The coulombic efficiency(89.3%) and capacitance retention 84.2% is confirmed even after 500 cycles.